Development of Learning Videos on Computer Hardware Materials - Herlinda, Romana; Sujaini, Herry; Suratman, Dede; Warneri, Warneri; Salam, Urai (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aimed to develop a learning video on computer hardware material at SMP Negeri 8 Jangkang using the ADDIE development method. This study involved 32 grade VII students as test subjects and six validators consisting of material, design, and media experts. Qualitative and quantitative data analysis showed that the developed learning video had a very high feasibility level, with an average percentage of 96% in the material, design, and media aspects. Empirical tests on 32 students showed similar results, with a feasibility level reaching 98% and positive responses from students to the learning media. Statistical tests using the Mann-Whitney method showed a significant difference between the experimental and control groups, with a substantial effect value of 5.44. These findings indicate that learning videos have a very considerable influence on student learning outcomes. Based on the study results, learning videos are categorized as very effective media and positively impact student learning outcomes on computer hardware material. In addition, student responses to the use of this media were very positive, which confirmed its effectiveness and usefulness in supporting a more interactive and enjoyable learning process.